Study of the photochemical transformation of 2-ethylhexyl 4-(dimethylamino)benzoate (OD-PABA) under conditions relevant to surface waters. (1st January 2016) - Calza, P.; Vione, D.; Galli, F.; Fabbri, D.; Dal Bello, F.; Medana, C.
Abstract: We studied the aquatic environmental fate of 2-ethylhexyl 4-(dimethylamino)benzoate (OD-PABA), a widespread sunscreen, to assess its environmental persistence and photoinduced transformation. Direct photolysis is shown to play a key role in phototransformation, and this fast process is expected to be the main attenuation route of OD-PABA in sunlit surface waters. The generation of transformation products (TPs) was followed via HPLC/HRMS. Five (or four) TPs were detected in the samples exposed to UVB (or UVA) radiation, respectively. The main detected TPs of OD-PABA, at least as far as HPLC-HRMS peak areas are concerned, would involve a dealkylation or hydroxylation/oxidation process in both direct photolysis and indirect phototransformation. The latter was simulated by using TiO2 -based heterogeneous photocatalysis, involving the formation of nine additional TPs. Most of them resulted from the further degradation of the primary TPs that can also be formed by direct photolysis. Therefore, these secondary TPs might also occur as later transformation intermediates in natural aquatic systems. Graphical abstract: Highlights: OD-PABA undergoes efficient direct photolysis as main phototransformation pathway. Negligible role of. OH and 1 O2 in OD-PABA phototransformation in surface waters. Up to five transformation intermediates were detected upon direct photolysis. Significant overlap of intermediates between direct photolysis and photocatalysis. The main intermediates may have similar environmental impact as OD-PABA.